Comparison of Cooperative Learning Models of Reciprocal Teaching Type and Cooperative Jigsaw Type on Students' Learning Outcomes in Animalia Material Class X MIPA SMA Negeri 1 Tapalang - Jirana; Mesra Damayanti; Rahmadina; Ruth Megawati (Jurnal Penelitian Pendidikan IPA, 2025)
This research aims to compare student learning achievements on the topic Animalia class X MIPA at SMA Negeri 1 Tapalang using two cooperative learning approaches, namely Reciprocal Teaching and Jigsaw. The research method used is quantitative descriptive with a Nonequivalent Control Group research design. The sample was taken using a nonprobability sampling technique with purposive sampling, involving two classes, namely X MIPA 1 as a Jigsaw class and X MIPA 3 as a Reciprocal Teaching class. The research was conducted at SMA Negeri 1 Tapalang, Tapalang District, Mamuju Regency, West Sulawesi Province. Data collection was carried out through pretest and posttest, then analyzed using SPSS version 24 statistical software. The results of the study showed that there was a significant difference between the Reciprocal Teaching and Jigsaw cooperative learning models on student learning achievement, as seen from the results of the posttest score which was significant (p = 0.000 ). The null hypothesis (Ho) can be rejected and the alternative hypothesis (H1) can be accepted. Therefore, it can be concluded that there is a significant difference in student learning outcomes between the Reciprocal Teaching and Jigsaw cooperative learning models in Animalia class X MIPA material at SMA Negeri 1 Tapalang. Based on the achievement of student learning achievements in the two classes, namely the Jigsaw and Reciprocal Teaching classes, it can be concluded that the Reciprocal Teaching type cooperative learning model is considered more effective than the Jigsaw type cooperative learning model.